Pengaruh Gaya Kepemimpinan, Pengembangan Karir, dan Kompensasi terhadap Etos Kerja - Benidetus Benidetus; Kiswoyo Kiswoyo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the influence of Leadership Style, Career Development, and Compensation on Work Spirit. The research was conducted at PT Finantara Intiga in West Kalimantan, Sanggau Kapuas Hulu. The population in this study consisted of 65 respondents or employees at PT Finantara Intiga. Data were collected through questionnaires using a Likert scale, with variables including the influence of Leadership Style (X1), Career Development (X2), and Compensation (X3) on Work Spirit (Y1). The data analysis technique used is multiple linear regression analysis with SPSS version 29 software. The results of this study indicate that Leadership Style has a positive but not significant influence, Career Development has a positive but not significant influence, and Compensation has a positive and significant influence on work ethos. Fair and competitive compensation has been proven to significantly improve employee work ethos. The findings of this study indicate an increase in employee work ethos at PT Finantara Intiga, which is crucial for human resource management in efforts to enhance employee productivity and performance through improved work ethos.